Are Immigrants More Left Wing than Natives? - Simone Moriconi; Giovanni Peri; Riccardo Turati (Institute of Labor Economics (IZA), 2023)
We analyze whether second-generation immigrants have different political preferences relative to children of citizens. Using data on individual voting behavior in 22 European countries between 2001 and 2017, we characterize each vote on a left-right scale based on the ideological and policy positions of the party. First, we describe and characterize the size of the "left-wing bias" in the vote of second-generation immigrants after controlling for a large set of individual characteristics and origin and destination country fixed effects. We find a significant left-wing bias of second-generation immigrants, similar in magnitude to the left-wing bias of those with a secondary, relative to a primary, education. We then show that this left-wing bias is associated with stronger preferences for inequality-reducing government intervention, internationalism and multiculturalism. We find only weak evidence that second-generation immigrants are biased away from populist political agendas and no evidence that they have stronger preferences for pro-immigrant policies. Finally, we show that growing up with a father who is struggling to integrate into the labor market is a strong predictor of this left-wing bias.
Keywords: D72; J61; P16; Z1; 330; immigration; elections; Europe